1989
DOI: 10.1111/j.1151-2916.1989.tb06259.x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Porous Coating for Low‐Density Ceramic Insulation Materials

Abstract: The need for improved coatings on low-density reusable surface insulation (RSI) materials used on the space shuttle has stimulated research into developing tougher coatings. The processing of a new porous composite "coating" for RSI called toughened unipiece fibrous insulation is discussed. Characteristics including performance in a simulated high-speed atmospheric entry, morphological structure before and after this exposure, resistance to impact, and thermal response to a typical heat pulse are described. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Until now, several high emissivity coatings have been developed for the application of thermal protective systems [10,11], thermal furnaces [12] and other high-temperature processing units for the purposes of energy savings [13,14], such as SiC and SiC based composites [6,[15][16][17][18], rare-earth oxides [7,10,[19][20][21], refractory metal silicides [22], transition metal oxides [23,24], cordierite structure systems [25,26], perovskite-type systems [13,27,28], magnetoplumbite structure systems [29][30][31][32] and metallic systems [33,34]. In addition to the pursuit of high M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 emissivity, other properties such as thermal shock resistance and oxidation resistance, should also be considered when high emissivity coatings are used at high temperatures. However, single component coatings rarely possess these comprehensive properties.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, several high emissivity coatings have been developed for the application of thermal protective systems [10,11], thermal furnaces [12] and other high-temperature processing units for the purposes of energy savings [13,14], such as SiC and SiC based composites [6,[15][16][17][18], rare-earth oxides [7,10,[19][20][21], refractory metal silicides [22], transition metal oxides [23,24], cordierite structure systems [25,26], perovskite-type systems [13,27,28], magnetoplumbite structure systems [29][30][31][32] and metallic systems [33,34]. In addition to the pursuit of high M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 emissivity, other properties such as thermal shock resistance and oxidation resistance, should also be considered when high emissivity coatings are used at high temperatures. However, single component coatings rarely possess these comprehensive properties.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…A reusable thermal protective system ( Fig. 1) consisting of a high emissivity coating used on the surface and a low thermal conductivity insulation used inside could decrease the surface temperature by radiation and prevent heat transfer via thermal conduction [1,5]. A mathematical model proposed by Van Wie [3] suggested that under identical heat flux the wall temperature of a hypersonic vehicle is reduced by 573 K when its surface emissivity is increased from 0.5 to 1.0 at Mach 10.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…The top surface and four sides of each insulator usually need to be covered with a high-emissivity coating, which could reduce the surface temperature by radiating heat toward the surrounding environment [7][8][9][10]. Therefore, high-emissivity coatings with reliable performance are an indispensable and critical part of TPS [11].…”
Section: Introductionmentioning
confidence: 99%
“…SiB 4 is considered a processing aid and emittance agent. After that, a new generation of toughened uni-piece fibrous insulation coating (TUFI) was developed on the basis of RCG for mechanical property requirements [11,13]. Compared with the past coatings, the composition and structure of TUFI have changed.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, HEC materials with similarly high thermal stability are sought to complement fibrous ZrO2 insulation materials in RTPSs. 2 mullite and ZrO2 ceramics, with favorable emissivity levels of 0.85 and higher achieved [3][4][5][6][7][8][9][10]. In our previous work, MoSi2-borosilicate glass coating prepared on fibrous ZrO2 ceramic showed excellent thermal shock behavior between room temperature and 1673 K [8], and following the inclusion of ZrO2 in the coating material, this thermal shock resistance was extended to 1773 K [9].…”
Section: Introductionmentioning
confidence: 99%